2015
DOI: 10.1016/j.jbiomech.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo hip arthrokinematics during supine clinical exams: Application to the study of femoroacetabular impingement

Abstract: Visualization of hip articulation relative to the underlying anatomy (i.e., arthrokinematics) is required to understand hip dysfunction in femoroacetabular (FAI) patients. In this exploratory study, we quantified in-vivo arthrokinematics of a small cohort of asymptomatic volunteers and three symptomatic patients with varying FAI deformities during the passive impingement, FABER, and rotational profile exams using dual fluoroscopy and model-based tracking. Joint angles, joint translations, and relative pelvic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 29 publications
(40 reference statements)
2
43
0
2
Order By: Relevance
“…Recent studies investigating the effect of FAI-related bony deformities in athletic populations have also reported a non-significant influence of cam on hip rotation ROM53 54 and all other directions of movement 54. It is possible that computer simulations or X-ray studies that rely on direct bone contact to predict impingement may be unrealistic 45. It might also reflect that some studies evaluated participants postsurgery, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigating the effect of FAI-related bony deformities in athletic populations have also reported a non-significant influence of cam on hip rotation ROM53 54 and all other directions of movement 54. It is possible that computer simulations or X-ray studies that rely on direct bone contact to predict impingement may be unrealistic 45. It might also reflect that some studies evaluated participants postsurgery, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…The mean adduction found in this study was comparable to the results of the symptomatic group found by Kapron et al Roach et al have investigated digital inclinometer and goniometer for measuring passive hip motion and found these methods to be associated with errors up to 5° (Roach et al 2013). Hence, these methods would not be feasible for measuring the differences in ROM found in this study nor for measuring the differences between subjects (Kapron et al 2015). …”
Section: Discussionmentioning
confidence: 92%
“…54 It is possible that computer simulations or X-ray studies that rely on direct bone contact to predict impingement may be unrealistic. 45 It might also reflect that some studies evaluated participants postsurgery, which may have influenced the results. Surgical interventions had no significant effect on hip ROM.…”
Section: Discussionmentioning
confidence: 99%